On Democratic Consolidation in the South: Comments on Frempong´s Paper - Rovira Mas, Jorge (CLACSO, 2021)
First of all, I would like to congratulate CLACSO-APISA-CODESRIA for the organization of this unique and important event and I want thank Ciska Raventós Vorst, my colleague at the Social Sciences Research Institute of the Universidad de Costa Rica, for her invitation to come here and comment on this interesting paper. Last, but not least, I want to express my greetings to Professor Frempong today – March 6th 2 007– when the people in the Republic of Ghana are celebrating the fiftieth anniversary of their Independence. I have organized my comments in five points or propositions.